高脂肪食負荷老化促進マウスのディスバイオシスおよび腸管炎症に対する分子状水素の効果 - 石塚, 俊晶; 小泉, 明穂; 高橋, さやか; 永田, 亘; 中川, 慶一 (日本薬理学会年会要旨集, 2022)
【Subject】It is suggested that aging and excessive intake of fat may induce dysbiosis and intestinal inflammatory damage additively. Previously, we revealed that the treatment with molecular hydrogen suppresses intestinal injury in high fat diet-loaded senescence-accelerated (SAMP8) mice.【Method】SAMP8 mice were fed control diet or high fat diet (HFD) for 14 weeks, and then the each group was fed placebo jelly (PJ) or hydrogen-rich jelly (HRJ) for 4 weeks. After the treatment, small intestinal tissues were harvested for morphological examination. In addition, we performed TBARS assay by using homogenized small intestine to analyze peroxidation damage by measuring malondialdehyde (MDA) level. Moreover, we analyzed alterations of microbiota composition in cecal feces by 16S rRNA gene analysis of microbiota profiling. 【Result & Conclusion】The treatment with HRJ prevented the increases of CD11b expression and MDA level in HFD-loaded SAMP8 mice. The treatment with HRJ did not affect the abundance of Proteobacteria phylum in HFD-loaded SAMP8 mice. However, the expressions of Gracilibacter, Lactinobactor and Marvinbryantia were increased in the HRJ group. These findings suggest that treatment with molecular hydrogen may affect the microbiota profiling and suppress intestinal inflammation and peroxidation damage in HFD-loaded SAMP8 mice.